Exposure of fibrinogen receptors in human platelets by surface proteolysis with elastase. - Kornecki, E (1986)
Human platelets that were preincubated with porcine elastase aggregated spontaneously upon the addition of fibrinogen. Maximal aggregation to fibrinogen was observed with platelets pretreated with an elastase concentration of 111 micrograms/ml, and half-maximal aggregation occurred after treatment with 11 micrograms/ml elastase. Binding of radiolabeled fibrinogen to elastase-treated platelets was specific, saturable, and showed a single class of 48,400 +/- 9,697 fibrinogen-binding sites per platelet with a dissociation constant of 6.30 +/- 1.48 X 10(-7) M. ATP, apyrase, and the stimulators of platelet adenylate cyclase forskolin, prostaglandin E1, prostacyclin, and N6, 2'-O-dibutyryl cyclic AMP did not inhibit the fibrinogen-induced aggregation of elastase-treated platelets. EDTA completely blocked the initiation of aggregation and reversed the fibrinogen-induced aggregation of elastase-treated platelets. Monoclonal and polyclonal antibodies directed against glycoproteins (GP) IIb and IIIa completely blocked the fibrinogen-induced aggregation of elastase-treated platelets. Immunoprecipitates with these antibodies obtained from detergent extracts of surface-radiolabeled, intact, and elastase-treated platelets contained the glycoproteins IIb and IIIa. We conclude that surface proteolysis by low concentrations of elastase can expose fibrinogen-binding sites associated with GPIIb and GPIIIa on the platelet surface, resulting in spontaneous aggregation upon the addition of fibrinogen. These findings may be relevant to hemostatic changes observed in patients with increased levels of circulating elastase.